The Austrian view and value co-creation process in solution-oriented firms: A seven stage, "solution prototyping" framework. Issue 1 (2nd January 2020) - Plouffe, Christopher R.; Nagel, Duane; Bonney, Leff; Hochstein, Bryan; Salas, Jim
ABSTRACT: We develop a conceptual framework that examines the behavior of the solutions-oriented-firm from initial solutions generation, through the "sale" and delivery to an initial customer, and its potential dissemination to the broader marketplace as a more standardized product/service offering. Particular attention is paid to the emerging discussion of value co-creation and Service-Dominant logic. Key tenets of the Austrian School of Economics are leveraged to identify how the selling firm, sales employee, and buying firm co-create value, and the "solution" itself. Thus, providing a deeper understanding of the "end-to-end" value chain of activities and drivers of firm performance.